Peningkatan Peran Serta Masyarakat dalam Pengelolaan Sampah Rumah Tangga Di Kabupaten Pakpak Bharat - Hutagaol, Sahat Maniur; Nasution, M. Arif; Kadir, Abdul (Universitas Medan Area, 2020)
This study aims to determine and analyze the role of the community in managing household waste in Pakpak Bharat Regency and to identify and analyze constraints in household waste management in Pakpak Bharat District. Research informants were selected by purposive sampling. Data collection techniques used through interviews and observation. Data Analysis Techniques used in this study are qualitative data analysis techniques. The results of the study indicate that the role of the community in Pakpak Bharat District in waste management is still less important. The community still lacks a role in reducing household waste sources, and has less role in handling waste in their respective environments. The obstacle factor in waste management is the lack of public awareness to reduce the source of waste by avoiding products with a lot of waste to reduce the volume of waste, not trying to choose products that can be refilled, not using shopping in place of packaging from sellers, not trying to choose packaging that can recycled, and less actively composting organic waste.